Hypocalcaemia in a patient with chronic liver disease: a case report - Devaraj, Navin Kumar; Mohamad, Fadzilah; Abdul Rashid, Aneesa; Abdul Manap, Abdul Hadi; Sallahuddin, Nurin Amalina (International Journal of Human and Health Sciences, 2021)
Acute hypocalcaemia is an uncommon presentation in clinical practice. However, severe acute hypocalcaemia may require immediate resuscitative measures. Thus, the case presented is aimed to highlight the importance of thorough assessment and prompt management in replacing the calcium. This case looks at a 34-year-old woman with underlying chronic liver disease (primary biliary cirrhosis) and hypoalbuminemia presented with symptom of perioral and peripheral paraesthesia for three days and was then infused with slow intravenous calcium gluconate. In avoiding recurrence, she was prescribed daily oral supplementation of calcium carbonate.